(untitled) (Global Journals of Research in Engineering, 2013)
The paper presents a miniaturized design of helical antenna loaded inside an impedance matching L-wall shaped cavity to achieve multi-frequency bands in the range of 5-15 GHz. A detail analysis of helix orientation inside the designed cavity is carried out. The cavity and helix arrangement is made reconfigurable by placing the helix and RF feed in such a way that it can thus be rotated manually at various angles with respect to the cavity walls. A comparative analysis of antenna gain and bandwidth is also reported. The antenna has a peak gain of 11.28dB and highest bandwidth of 2.68GHz. The maximum power handling capacity of the design is found to be 40.67MW. Computer Simulation Tool is used in the modeling of antenna. The antenna being conformal in design finds its application in aerospace, military and personal wireless communication.